Downregulation of NDUFB6 due to 9p24.1‐p13.3 loss is implicated in metastatic clear cell renal cell carcinoma. (15th October 2014) - Narimatsu, Takahiro; Matsuura, Keiko; Nakada, Chisato; Tsukamoto, Yoshiyuki; Hijiya, Naoki; Kai, Tomoki; Inoue, Toru; Uchida, Tomohisa; Nomura, Takeo; Sato, Fuminori; Seto, Masao; Takeuchi, Ichiro; et al.
Abstract This study was conducted to clarify the genomic profiles of metastatic clear cell renal cell carcinomas (ccRCCs) and identify the genes responsible for development of metastasis. We analyzed the genomic profiles of 20 cases of primary ccRCC and their corresponding metastases using array‐based comparative genomic hybridization, and identified 32 chromosomal regions in which gene copy number alterations were detected more frequently in metastases than in the primary tumors. Among these 32 regions, 9p24.1‐p13.3 loss was the most statistically significant alteration. Furthermore, we found that patients with 9p24.1‐p13.3 loss in primary tumors exhibited significantly lower rates of recurrence‐free and cancer‐specific survival, suggesting that 9p loss in the primary tumor is a potential biomarker predicting early recurrence of metastasis. Interestingly, the genomic profiles of primary tumors with 9p loss resembled those of their corresponding metastases, though 9p loss was accumulated in the metastases derived from the primary tumors without 9p loss. Comparison of the mRNA expression levels revealed that 2 of 58 genes located at 9p24.1‐p13.3 were downregulated due to gene copy number loss in ccRCCs. An overexpression study of these two genes in ccRCC cell lines revealed that downregulation of NDUFB6 due to loss at 9p24.1‐p13.3 may confer a growth advantage on metastatic ccRCC cells. These results were confirmed by analyzing the data of 405 cases of ccRCC obtained from The Cancer Genome Atlas (TCGA). On the basis of our present data, we propose that NDUFB6 is a possible tumor suppressor of metastatic ccRCCs.